The effects of exergames on anxiety levels: A systematic review and meta-analysis - Borges Viana, R.; Dankel, S. J.; Loenneke, J. P.; Gentil, P.; Vieira, C. A.; dos Santos Andrade, M.; Vancini, R. L.; Barbosa de Lira, C. A. (Scandinavian Journal of Medicine & Science in Sports, 2020)
There are currently many different approaches to performing exergames and there is still no consensus as to whether exergames are able to reduce anxiety levels, as well as whether exergames provide greater reductions on anxiety levels when added to traditional forms of clinical interventions. Therefore, the aim of the present systematic review and meta-analysis was to access data from studies that evaluated the effects of exergames on anxiety levels in humans. PubMed, Scopus and Cochrane databases were searched up to 22 February 2019. Inclusion criteria were acute and chronic (short-term and long-term interventions) studies which evaluated the effects of exergames in anxiety levels as primary or secondary aim. Of the 1342 studies found, 17 and 10 were included in qualitative analyses and meta-analyses, respectively. The within-group analysis found that exergames (standardized mean difference [SMD]:-0.57 [95% Confidence interval (CI):-0.86 to -0.28], p<0.001) and usual care (SMD:-0.21 [95%CI:-0.34 to -0.08], p=0.002) resulted in significant improvements on anxiety levels. However, the between-group meta-analysis on the effects of control interventions versus exergames (SMD:0.02 [95%CI:-0.55 to 0.60], p=0.939) found no significant difference between groups in anxiety levels reductions. There was also no significant difference (SMD:-0.04 [95%CI:-0.32 to 0.25], p=0.805) between usual care versus exergames plus usual care interventions in anxiety levels reductions. Although exergames demonstrated within-group improvements in anxiety levels across different clinical populations, it was not greater than the effects from non-exercise interventions. Also, given the paucity of studies, small sample sizes, different research designs, and different population investigated, the existing evidence is insufficient to support the advantages of usual care supplemented by exergame intervention over usual care standalone in anxiety levels reduction.